27 Training Need Analysis for Contract Employees (Study Case at PT. SCI Laboratory Surabaya) - Putri, Agustin Welliana Rahmawati; Noer, Bustanul Arifin (IPTEK Journal of Proceedings Series, 2019)
PT. Sucofindo (SCI) is a company engaged in the fields of inspection, supervision, testing and assessment. There are a lot of services offered by PT. SCI, the role of human resources needs to be put in concern given the increasingly widespread challenges of competence. The company's efforts in that employees have the ability and good performance, namely by conducting training for employee self-development. To be able to understand the importance of training for contract employees of PT. SCI Laboratory Surabaya, this study used the theory of Training Need Analysis (TNA), an analysis of training needs for contract employees. The research sample was taken in a survey of 97 employees of PT. SCI Surabaya laboratory. With the method of Focus Group Discussion (FGD) and Training need assessment-tools (TNA-T) to analyze the training needs for contract employees at PT. SCI Laboratory Surabaya. The results of the study using the TNA-T method were PT. SCI Surabaya Laboratory’s contract employees still need training. The design of TNA for 2019 is the training of Chemical AK3 as many as 34 people for Office Operations using the off job training method, 27 people need method validation training, and 15 people need training in analysis according to the santart method. TNA for 33 field operations employees needed method validation training and 17 people needed draft survey operation training. Training other than AK3 Chemistry is recommended to use the on job training method